2006
DOI: 10.1021/ie061166x
|View full text |Cite
|
Sign up to set email alerts
|

Autohydrolysis of Arundo donax L., a Kinetic Assessment

Abstract: Arundo donax L. was submitted to a process of isothermal autohydrolysis in the temperature range of 150-195°C, for periods between 0 and 15 h and a liquid/solid ratio ) 8 g g -1 , for the purpose of hydrolyzing the hemicelluloses to oligomers (compounds which are of interest to the food industry) and monomers. A conventional kinetic model was developed that explains the evolution over time of the hemicelluloses and hemicellulose degradation products. Kinetic modeling was also carried out using the severity fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
26
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 35 publications
7
26
0
Order By: Relevance
“…In contrast to the sugars, the production of sugar derivative compounds (and also decomposition products) was facilitated with increasing temperature as shown by lowest value of E a for the third step. Similar behavior was also found for other sources of biomass and pretreatment processes, as reported elsewhere [19,28,32,34].…”
Section: Kinetic Coefficientssupporting
confidence: 88%
See 3 more Smart Citations
“…In contrast to the sugars, the production of sugar derivative compounds (and also decomposition products) was facilitated with increasing temperature as shown by lowest value of E a for the third step. Similar behavior was also found for other sources of biomass and pretreatment processes, as reported elsewhere [19,28,32,34].…”
Section: Kinetic Coefficientssupporting
confidence: 88%
“…A comparison of rate constants for the conversion of hemicelluloses into oligomers indicated a similar magnitude to those reported for the conversion of xylan into xylooligomers (k 1 ) for hydrolysis of palm shell (0.07017 min −1 at 180°C) [32], and a higher magnitude than that exhibited by aspen wood (0.00717 min −1 at 160°C), sugar maple (0.00900 min −1 at 160°C) [18], and Arundo donax (0.02655 min −1 at 180°C) [19]. Recently, Vallejos et al [17] reported k 1 , k 2 , and k 3 values similar to those obtained in this work for autohydrolysis of hemicelluloses from sugarcane bagasse, but using the kinetic model proposed by Mittal et al [18] and a different scale and reaction conditions.…”
Section: Kinetic Coefficientssupporting
confidence: 71%
See 2 more Smart Citations
“…Other studies dealing with wood autohydrolysis have been reported for Acacia dealbata (a hardwood with hemicelluloses mainly made up of xylan) [9] and Pinus pinaster (a softwood with hemicelluloses mainly made up of glucomannan and xylan) [10]. Additional kinetic studies of single-stage autohydrolysis have been reported for a number or non-wood materials, including corncobs [11], vine shoots [12], Arundo donax [13], barley husks [14], bamboo [15], Cytisus scoparius [16], rye straw [17], and almond shells [18].…”
Section: Introductionmentioning
confidence: 99%